Autoimmune diseases refractory to corticosteroids and immunosuppressants - Elkoshi, Zeev (Frontiers in Immunology, 2024)
Corticosteroids and immunosuppressive drugs can alleviate the symptoms of most autoimmune diseases and induce remission by restraining the autoimmune attack and limiting the damage to the target tissues. However, four autoimmune nondegenerative diseases-adult advanced Type 1 diabetes mellitus, Hashimoto's thyroiditis, Graves' disease, and advanced primary biliary cholangitis-are refractory to these drugs. This article suggests that the refractoriness of certain autoimmune diseases is due to near-total loss of secreting cells coupled with the extremely low regenerative capacity of the affected tissues. The near-complete destruction of cells responsible for secreting insulin, thyroid hormones, or biliary HCO3-diminishes the protective effects of immunosuppressants against further damage. The slow regeneration rate of these cells hinders tissue recovery, even after drug-induced immune suppression, thus preventing remission. Although the liver can fully regenerate after injury, severe primary biliary cholangitis may impair this ability, preventing liver recovery. Consequently, these four autoimmune diseases are resistant to immunosuppressive drugs and corticosteroids. On the other hand, early stages of Type 1 diabetes and early primary biliary cholangitis, where damage to secreting cells is partial, may benefit from immunosuppressant treatment. In contrast to these four diseases, chronic degenerative autoimmune conditions like multiple sclerosis may respond positively to corticosteroid use, despite the limited regenerative potential of the affected tissue (the CNS). The opposite is true for acute autoimmune conditions like Guillain-Barré Syndrome. Clinical significance: The addition of corticosteroids and/or immunosuppressive drugs to ursodeoxycholic acid treatment of early-stage primary biliary cholangitis, may restore the liver function and improve the clinical outcomes.